THE CULT OF THE HEAVEN IN THE RELIGIOUS TRADITION OF PEOPLES OF EASTERN AND INNER ASIA - Yangutov , Leonid; Abaeva, Liubov; Abaev, Nikolai (Revista Inclusiones, 2020)
The article analyzes the religious traditions of the countries of Eastern and Inner Asia, where the cult has gained great popularity. The cult of Heaven is studied and considered from ethnoconfessional, cultural, social, and political aspects. The research presented in this article reveals the autochthonous and rational-pragmatic aspect of this cult, which is characteristic of agricultural China and its settled population, as well as the universal and abstract-philosophical aspect peculiar to nomadic confederations and tribal unions of the Turkic-Mongolian peoples, inhabiting the territory of Inner Asia. The cult of Heaven is studied as its political composite during the Shan-Yin state formation in the territory of China, where it acts as the divine guarantor of the supreme power of the Shang-Yin rulers; the political content of this cult in the state formation of the Great Steppe of Inner Asia is also considered. It is traced how the political content of the Chinese cult of Heaven as a guarantor of supreme authority influences the ideology of the rulers of the first state formations of nomadic tribes in the neighboring region of Inner Asia, which were in closest cultural, political and economic contact with the powerful neighbor.